Correction: Mineralized belemnoid cephalic cartilage from the late Triassic Polzberg Konservat-Lagerstätte (Austria). - Petra Lukeneder; Alexander Lukeneder (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0264595.].